TAL Effector Repertoires of Strains of Xanthomonas phaseoli pv. manihotis in Commercial Cassava Crops Reveal High Diversity at the Country Scale - Zárate-Chaves, Carlos A. (Microorganisms, 2021)
Transcription activator-like effectors (TALEs) play a significant role for pathogenesis in several xanthomonad pathosystems. Xanthomonas phaseoli pv. manihotis (Xpm), the causal agent of Cassava Bacterial Blight (CBB), uses TALEs to manipulate host metabolism. Information about Xpm TALEs and their target genes in cassava is scarce, but has been growing in the last few years. We aimed to characterize the TALE diversity in Colombian strains of Xpm and to screen for TALE-targeted gene candidates. We selected eighteen Xpm strains based on neutral genetic diversity at a country scale to depict the TALE diversity among isolates from cassava productive regions. RFLP analysis showed that Xpm strains carry TALomes with a bimodal size distribution, and affinity-based clustering of the sequenced TALEs condensed this variability mainly into five clusters. We report on the identification of 13 novel variants of TALEs in Xpm, as well as a functional variant with 22 repeats that activates the susceptibility gene MeSWEET10a, a previously reported target of TAL20(Xam668). Transcriptomics and EBE prediction analyses resulted in the selection of several TALE-targeted candidate genes and two potential cases of functional convergence. This study provides new bases for assessing novel potential TALE targets in the Xpm–cassava interaction, which could be important factors that define the fate of the infection.